THE INFLUENCE OF CAPITAL VENTURE SHARIAH AND MUSYARAKAH TO GROWTH MSME’S IN WEST JAVA - Salam Almuhtasib, Abdul; Hasan, Asyari; Rizal, Sofyan (ITB AAS Indonesia Surakarta, 2025)
The contribution of MSMEs to economic growth is one of the key factors where in 2023 the contribution of MSMEs to Gross Domestic Bruti (GDP) reached Rp 9,580 Trillion, but this was not accompanied by business development which ultimately became a new problem for the economy. Customer financing in Islamic banking is always consumptive and unsustainable financing in the consumptive retail sector reaches 40.8% while the average micro financing is still at 21.66%, in the end it is the habit that shapes the community and MSME players to behave the same consumptive and get used to credit and not used to the profit sharing system. This problem is one of the foundations for the presence of this research, this research method uses quantitative methods with secondary data where the calculation is in accordance with the ratio to calculate the growth of MSMEs in West Java with indicators of musyarakah contracts and Islamic venture capital. The results in this study are total capital is negative with a value of 3,208 or no effect, the duration of the contract has a positive effect on the growth of MSMEs in West Java 0.145, the proportion of capital also has a positive effect on the growth of MSMEs in West Java 0.088 and profit sharing has an effect of 0.252 on the growth of MSMEs. So it can be concluded that the growth of MSMEs is influenced by the duration of the contract, the proportion of capital and profit sharing.